Odpowiedzi

2010-03-24T18:25:54+01:00
A) 4x-3=3x+5
4x-3x=5+3
x=8
b) 5x+2=7-3x
5x+3x=7-2
8x=5
x=5/8
c) 3(x-1)=0
3x-3=0
3x=3
x=1
d) -6(x+1)=24
-6x-6=24
-6x=30
x=-5
e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15
x=15/10=3/2
f) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10
x=-5
2010-03-24T18:26:32+01:00
A)
4x-3=3x+5
4x=3x+8
x=8
b)
5x+2=7-3x
8x=5
x=5/8
c)
3(x-1)=0
3x-3=0
3x=3
x=1
d)
-6(x+1)=24
-6x-6=24
-6x=30
x=-5
e)
-7(x-2)=3x-1
-7x+14=3x-1
-10x=-15
x=15/10=3/2
f)
4(x-1)=6(1+x)
4x-4=6+6x
-2x=10
x=-5
2010-03-24T18:28:36+01:00
A) 4x-3=3x+5/-3x
x-3=5/+3
x=8

b) 5x+2=7-3x/+3x
8x+2=7/-2
8x=5/:8
x=5/8

c) 3(x-1)=0
3x-3=0/+3
3x=3/:3
x=1

d) -6(x+1)=24
-6x-6=24/+6
-6x=30/:(-6)
x=-5

e) -7(x-2)=3x-1
-7x+14=3x-1/+7x
14=10x-1/+1
15=10x/:10
15/10=x
3/2=x

f) 4(x-1)=6(1+x)
4x-4=6+6x/-4x
-4=6+2x/-6
-10=2x/:2
-5=x